One-stage synthesis of FcP(O)(OC2H5)2 from ferrocene and α-hydroxyethylphosphonate. Issue 48 (29th April 2016) - Khrizanforov, Mikhail; Strekalova, Sofia; Kholin, Kirill; Khrizanforova, Vera; Grinenko, Valeriya; Gryaznova, Tatyana; Budnikova, Yulia
Abstract : A new approach is proposed for ferrocene phosphorylation using α-hydroxylalkylphosphonate as a "masked" phosphorylating agent, by electrochemical reduction of a ferrocene and (Me)2 C(OH)P(O)(OC2 H5 )2 mixture at −50 °C. Abstract : A new approach is proposed for ferrocene phosphorylation using α-hydroxylalkylphosphonate as a "masked" phosphorylating agent, by electrochemical reduction of a ferrocene and (Me)2 C(OH)P(O)(OC2 H5 )2 mixture at −50 °C. The method makes it possible to obtain the product of diethyl ferrocenyl phosphonate with a high yield (87–89%) and 100% conversion of the initial phosphonate in one stage. It is evidenced with experiments that ferrocene reduction is carried out with preservation of the iron charge in the ferrocene fragment and with the formation of a cyclopentadienyl ligand radical anion at −3.3 V ref. Ag/AgCl (at −50 °C).